THE ROLE OF FOREIGN LANGUAGES IN THE STATE LANGUAGE IN THE ACTIVITIES OF OFFICE SECRETARIES (Scientific journal of the Fergana State University, 2023)
The use of listening skillin teaching in the elementary grades of the school makes classes interesting and varied. This article discusses assignment for students learning a foreign language.